2015
DOI: 10.1016/j.devcel.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

BORC, a Multisubunit Complex that Regulates Lysosome Positioning

Abstract: SUMMARY The positioning of lysosomes within the cytoplasm is emerging as a critical determinant of many lysosomal functions. Here we report the identification of a multi-subunit complex named BORC that regulates lysosome positioning. BORC comprises eight subunits, some of which are shared with the BLOC-1 complex involved in the biogenesis of lysosome-related organelles, and the others of which are products of previously uncharacterized open reading frames. BORC associates peripherally with the lysosomal membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
468
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(498 citation statements)
references
References 45 publications
27
468
0
3
Order By: Relevance
“…BORCS7 encodes BLOC‐1‐related complex subunit 7 (Diaskedin), part of the recently described BLOC‐1‐related complex, which has been implicated in lysosomal function and cell migration [Pu et al, 2015]. AS3MT encodes arsenic methyltransferase, which has a known role in arsenic metabolism [Sumi and Himeno, 2012], although its functions in the brain are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…BORCS7 encodes BLOC‐1‐related complex subunit 7 (Diaskedin), part of the recently described BLOC‐1‐related complex, which has been implicated in lysosomal function and cell migration [Pu et al, 2015]. AS3MT encodes arsenic methyltransferase, which has a known role in arsenic metabolism [Sumi and Himeno, 2012], although its functions in the brain are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…36 Interestingly, the authors found that cells silenced for BORC subunit-myrlysin were defective in spreading and migration, implicating a conceivable involvement of these proteins during tumor metastasis. Further, the Arl8b-dependent pH control of lysosomal motility could be important for cellular behavior in acidic microenvironments, holding credible relevance to study of Arl8 function in cancer progression.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although the identity of the Arl8 GEF and GAP remains unknown, recent studies have identified BORC (BLOC-one-related complex), a multi-subunit protein complex that regulate Arl8b recruitment to lysosomes, and thereby mediate kinesindependent lysosome transport toward the cell periphery. 36 BORC shares 3 of its 8 subunits with the BLOC-1 complex that is involved in the biogenesis of lysosome-related organelles. 37 The clustered regularly interspaced short palindromic repeats (CRISPR)-based knockout of the BORC-specific subunit, myrlysin, was shown to cause Arl8b detachment from lysosomes along with clustering of lysosomes in the perinuclear region (an effect also observed upon Arl8b depletion).…”
Section: Introductionmentioning
confidence: 99%
“…This kinesin is a heterotetramer composed of two heavy chains (KIF5A, KIF5B or KIF5C) and two light chains (KLC1, KLC2, KLC3 or KLC4) (DeBoer et al, 2008). Kinesin-1 is recruited to lysosomes by a chain of interacting proteins, including the multisubunit BLOC-1-related complex (BORC), the Arf-like small GTPase Arl8 (which has two isoforms in mammals, Arl8a and Arl8b, hereafter generically referred to as Arl8), and the Arl8 effector SifA and kinesin-interacting protein (SKIP, also known as PLEKHM2) (Boucrot et al, 2005;Bagshaw et al, 2006;Hofmann and Munro, 2006;Rosa-Ferreira and Munro, 2011;Pu et al, 2015) (Fig. 4).…”
Section: Anterograde Transportmentioning
confidence: 99%